2020
DOI: 10.1039/d0tc03709e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of computational chemistry in organic solar cell research

Abstract: The precise design of organic photovoltaic materials and the control of morphology in active layer are crucial for achieving high-performance organic solar cells (OSCs). Up to now, however, it remains...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 167 publications
0
61
0
Order By: Relevance
“…Some other recent reviews with the same context can also be found in the literature. [ 41,50,51 ] Every single occurrence in the device can be explained from a quantum level. We start by looking at an atom and its quantum mechanisms.…”
Section: The Structure–morphology–performance Theoretical Frameworkmentioning
confidence: 99%
“…Some other recent reviews with the same context can also be found in the literature. [ 41,50,51 ] Every single occurrence in the device can be explained from a quantum level. We start by looking at an atom and its quantum mechanisms.…”
Section: The Structure–morphology–performance Theoretical Frameworkmentioning
confidence: 99%
“…DL methods have also been exploited in predicting ground- and excited state properties for thousands of organic molecules, where the accuracy for small molecules can be even superior to QM ab initio methods [ 78 ]. Recent advances in the use of machine learning and computational chemistry methods to study organic photovoltaics are discussed in other works [ 80 , 81 , 82 ].…”
Section: Materials Discoverymentioning
confidence: 99%
“…In order to approach to the theoretical limit of OSCs, strenuous research efforts had been made in these three aspects: (1) design and synthesize novel donor and acceptor materials, (2) optimize fabrication conditions and device structures, and (3) explore the mechanism of device operation. [ 10 ] The first two methods are a trial‐and‐error procedure, which requires expensive materials, long‐time consumption, and large manpower input while the last manner is a new way to study the physicochemical properties of materials and to simulate the device operation processes only based on multiscale computational methods, such as Density Function Theory (DFT), Molecular Dynamics (MD), Monte Carlo (MC) and so on, [ 11–17 ] which provides helpful guidelines and insight for designing novel molecules. In principles, the final device performance is only dependent on its materials and the function of manufacturing technology and device structures is to better give play to the role of materials.…”
Section: Introductionmentioning
confidence: 99%